2022
DOI: 10.1541/ieejjia.22003993
|View full text |Cite
|
Sign up to set email alerts
|

Control Method of Electrolytic Capacitor-Less Dual Inverter-Fed IPMSM under Periodic Load Torque Fluctuations

Abstract: This paper proposes a control method for an electrolytic capacitor-less dual inverter for compressors. Single-phase motor drive systems are required to minimize vibrations, maintain a high power factor, and meet the limit for harmonic current emissions. The proposed control method achieves the harmonic reduction of the dq-axis currents, a high power factor, and a low grid current THD under periodic load torque fluctuations. The effectiveness of the proposed method is demonstrated via experimental results, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The experimental results shown in Figs. 13 and 14 confirmed that the torque and current ripple improved when the proposed method was applied. Fig.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The experimental results shown in Figs. 13 and 14 confirmed that the torque and current ripple improved when the proposed method was applied. Fig.…”
Section: Resultsmentioning
confidence: 68%
“…12 shows the experimental waveform of the stationary d-q axis reference voltage. After the reference voltage angle is estimated by (13), the sector can be obtained. The coefficient is determined from the sector, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…FIGURE16. Short-circuit current waveforms of the overvoltage suppression method using new devices and after several cycles of operation using (a) the single short-circuit method and (b) the multiple short-circuit method with four short-circuits in a leg.…”
mentioning
confidence: 99%